2016
DOI: 10.1007/s10661-016-5625-4
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a submersible microbial fuel cell for Cr(VI) detection in water

Abstract: Two-chamber microbial fuel cells (MFCs) were used to study the applicability of MFCs for hexavalent chromium (Cr(VI)) detection in water. The microbial acetate oxidation in the anode and the Cr(VI) reduction in the cathode together generated voltages, which were used to indicate the change in Cr(VI) concentrations of the cathode under varying conditions of pH, ionic strength, co-existing Fe(II) concentration, and organic matter concentration. The MFC-based Cr(VI) detector showed a significant change in voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Earlier in a study, the internal resistance (161 Ω) reported was higher than recorded in the current study (98.2 Ω). For voltage generation, the maximum power density of SMFC with Cr(VI) (48.88 mW/m 2 ) was increased compared with the SMFC (39.22 mW/m 2 ), which was consistent with a previous study [ 38 ]. The occurrence of an increased voltage generation with the addition of Cr(VI) can be described by the Nernst equation (Equation (2)).…”
Section: Resultssupporting
confidence: 92%
“…Earlier in a study, the internal resistance (161 Ω) reported was higher than recorded in the current study (98.2 Ω). For voltage generation, the maximum power density of SMFC with Cr(VI) (48.88 mW/m 2 ) was increased compared with the SMFC (39.22 mW/m 2 ), which was consistent with a previous study [ 38 ]. The occurrence of an increased voltage generation with the addition of Cr(VI) can be described by the Nernst equation (Equation (2)).…”
Section: Resultssupporting
confidence: 92%
“…The development of MFCs with two chambers instead of one chamber has been effectuated by Hyeonyong Chung et al [ 119 ] for Cr(VI) detection in water. The generated voltage was utilized to pursue the change in Cr(VI) concentration under different conditions in the co-presence of Fe(II) up to 1:15 molar ratio and in the co-presence of fulvic acid up to 50 mg·L −1 .…”
Section: Electrochemical Biosensors For Hexavalent Chromium Determmentioning
confidence: 99%
“…However, their method was restricted to acidic water of pH 1−2 with a concentration range of 0.1−15 mg/L of Cr 6+ . 28 The detection method was valid only in the co-presence of Fe 2+ with Cr 6+ /Fe 2+ in the molar ratio of 1:15. The voltage output of the MFC varied with the concentration of Cr 6+ in the cathode at the pH values of 1 and 2, and of the co-existing Fe 2+ concentration, ionic strength, and organic matter concentration as well, which limits the usage of this sensor.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recovery time of this CMFC was too long. Recently, Chung et al 28 used a dual‐chamber MFC for the detection of Cr 6+ . However, their method was restricted to acidic water of pH 1−2 with a concentration range of 0.1−15 mg/L of Cr 6+ 28 .…”
Section: Introductionmentioning
confidence: 99%